Patch Erosion for Deformable Lapped Textures on 3D Fluids. (4th June 2021) - Gagnon, Jonathan; Guzmán, Julián E.; Mould, David; Paquette, Eric
Abstract: We propose an approach to synthesise a texture on an animated fluid free surface using a distortion metric combined with a feature map. Our approach is applied as a post‐process to a fluid simulation. We advect deformable patches to move the texture along the fluid flow. The patches are covering the whole surface every frame of the animation in an overlapping fashion. Using lapped textures combined with deformable patches, we successfully remove blending artifact and rigid artifact seen in previous methods. We remain faithful to the texture exemplar by removing distorted patch texels using a patch erosion process. The patch erosion is based on a feature map provided together with the exemplar as inputs to our approach. The erosion favors removing texels toward the boundary of the patch as well as texels corresponding to more distorted regions of the patch. Where texels are removed leaving a gap on the surface, we add new patches below existing ones. The result is an animated texture following the velocity field of the fluid. We compared our results with recent work and our results show that our approach removes ghosting and temporal fading artifacts.